Sundanese Community Wisdom: Strengthening Local Spirituality in Responding to The Global Ecological Crisis - Deni Miharja; Khomisah (Empirisma: Jurnal Pemikiran dan Kebudayaan Islam, 2025)
This study aims to explore the contribution of religion through local spirituality in building ecological awareness and responding to the global environmental crisis based on local wisdom values. Using a theoeccological approach, this study reflects religious teachings through the lens of indigenous spirituality as a living and contextual narrative of religious faith. The main focus of the study is on the Sundanese Indigenous community, specifically the practice of integral environmental conservation, including land, forest, water management, and food security and sustainability. The results show that the ecological ethics of the Sundanese Indigenous community are not merely cultural practices, but rather expressions of spirituality carried out collectively. Principles such as ulah ngarusak (do not damage), leuweung kolot (forbidden forest), huma management, and the leuit system (traditional rice barn) reflect the sacred relationship between humans, nature, and the cosmos. The novelty of this study lies in the integration of the theoecological perspective with Sundanese local wisdom, which has previously been studied more in anthropological or ecological dimensions alone. Thus, this study offers an alternative model for how local spirituality can be formulated as a concrete and applicable theoecological narrative. The implication is that the integration of local spirituality-based ecological values ​​into environmental conservation and food security policies is crucial for building a just and sustainable human ecology.